(Arene)ruthenium Complexes with Imidazolin‐2‐imine and Imidazolidin‐2‐imine Ligands. Issue 26 (5th August 2014) - Tönnemann, Justus; Scopelliti, Rosario; Severin, Kay
Abstract: Imidazolin‐2‐imine and imidazolidin‐2‐imine ligands are versatile N donors in transition metal chemistry. Here, we describe the synthesis and characterization of (arene)Ru complexes with these ligands. Simple adducts of the type [( p‐ cymene)Ru(L)Cl2 ] (L = 1, 3‐diarylimidazolin‐2‐imine or 1, 3‐dimesitylimidalzolidin‐2‐imine) can be converted into complexes in which the imines act as π ligands with tethered imine groups. Furthermore, the high basicity of the N donor group can promote self‐activation of the (arene)Ru complexes. Abstract : (Arene)Ru complexes with imidazolin‐2‐imine and imidazolidin‐2‐imine ligands of the general formula [(cymene)RuCl2 L] are described. Photochemical activation allows the preparation of complexes in which the imines act as π ligands with tethered imine groups.